Individual and Temporal Variation in Outcrossing Rates and Pollen Flow Patterns in Ceiba pentandra (Malvaceae: Bombacoidea) - Lobo Segura, Jorge Arturo (2013)
Ceiba pentandra is a tropical tree with high rates of selfing in some populations. In mixed‐mating species, variation in selfing is due to changes in adult density or variability of incompatibility systems. The effect of spatial isolation and phenology on selfing rates and pollen flow distances was analyzed using microsatellites in a fragmented population of Ceiba pentandra, in southern Costa Rica. Adult trees within a heterogeneous landscape were classified as grouped or isolated. We compared selfing rates at the individual level, between isolation conditions and 2 yr (2007, 2009), which differed in the number of flowering individuals. Mixed mating was estimated in both years (tm = 0.624–0.759). Trees mated predominantly by outcrossing, while only a few trees reproduced through selfing. Spatial isolation did not significantly affect outcrossing rates. The progeny of grouped trees was mostly sired by near‐neighbors (<1 km) and by long‐distance pollen flow events in isolated trees. A reduction in the number of flowering individuals in 2009 reduced near‐neighbor matings, increased selfing in grouped trees, and decreased the number of unsampled sires in the progeny. Comparing selfing rates on individuals that flowered in both reproductive periods suggests a flexible mating system. Variation in self‐fertilization rates in this population appears to depend on variation of individual traits, such as genetic variability in self‐incompatibility genes, but it is independent of landscape heterogeneity. In contrast, pollen flow distances depend on local tree density as bats concentrate their foraging between near individuals to maximize energy efficiency.